Diversity of insect antimicrobial peptides and proteins - a functional perspective: a review - Eleftherianos, Ioannis; Zhang, Wei; Heryanto, Christa; Mohamed, Amr; Contreras, Gabriela; Tettamanti, Gianluca; Wink, Michael; Bassal, Taha (International journal of biological macromolecules, 2021)
The innate immune response of insects provides a robust line of defense against pathogenic microbes and eukaryotic parasites. It consists of two types of overlapping immune responses, named humoral and cellular, which share protective molecules and regulatory mechanisms that closely coordinate to prevent the spread and replication of pathogens within the compromised insect hemocoel. The major feature of the humoral part of the insect immune system involves the production and secretion of antimicrobial peptides from the fat body, which is considered analogous to adipose tissue and liver in vertebrates. Previous research has identified and characterized the nature of antimicrobial peptides that are directed against various targets during the different stages of infection. Here we review this information focusing mostly on the diversity and mode of action of these host defense components, and their critical contribution to maintaining host homeostasis. Extending this knowledge is paramount for understanding the evolution of innate immune function and the physiological balance required to provide sufficient protection to the host against external enemies while avoiding overactivation signaling events that would severely undermine physiological stability.
Gesehen am 14.12.2021